Development of Interactive Learning Media as an Alternative to Improve Students' Conceptual Understanding and Motivation on the Temperature and Heat Topics - Dion Bahrudin, Azhar; Insjaf Yogihati, Chusnana (International Journal of Education and Teaching Zone, 2022)
This study aims to develop and determine the feasibility of interactive learning media on the topic of temperature and heat. The type of research is Research and Development (R&D) with the ADDIE model. In this model, the stages include Analyze, Design, Develop, Implement, and Evaluate. However, this research is only up to the development stage. The subjects of this study were 20 students from one of the XI MIPA classes at Panjura High School. The interactive media was developed in the form of an android-based application with the topic of temperature and heat. The research data was obtained from the results of content and construct validation by the validator and then the feasibility test by the students. From the research that has been done, the average percentage of content or display validation is 82.2% including in the very valid category and the average percentage of construct validation is 93.1% including in the very valid category. For the feasibility test conducted by students, the percentage is 95.2% so it is included in the very feasible category. Based on the validation test and student feasibility test, it was found that interactive learning media can strengthen students' conceptual understanding and motivation in learning. The media developed is also easy to download and use and easy to operate. Suggestions for further research are applications that are made can be downloaded via the google play store, then the questions on the diagnostic test are easier than Quiz and not only the Android system but iOS as well.